2010
DOI: 10.18406/2316-1817v2n22010271
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dos tratos silviculturais na produtividade e na qualidade da madeira em plantações de Eucalyptus spp

Abstract: RESumO O presente trabalho descreve os tratamentos culturais que podem ser realizados em plantações de eucalipto, com o intuito de melhorar a produtividade e qualidade da madeira produzida. A escolha do espaçamento inicial de plantio depende do destino final da madeira a ser produzida. O controle de plantas invasoras pode ser de forma manual, mecânica ou química nas linhas e/ou entrelinhas de plantio, este é de suma importância principalmente no estabelecimento da floresta, no qual essas plantas invasoras iram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…Increased productivity of planted forests can lead to changes in wood quality (Sette Júnior et al, 2012). Thus, from all wood properties, density is one of the most important and can be changed with the use of some silvicultural treatments, such as spacing, irrigation and fertigation (Sousa et al, 2010). This was not verified for the hybrid Urograndis, which did not show a tendency to decrease in D b with the use of irrigation, thus being considered more stable regarding water availability.…”
Section: Resultsmentioning
confidence: 97%
“…Increased productivity of planted forests can lead to changes in wood quality (Sette Júnior et al, 2012). Thus, from all wood properties, density is one of the most important and can be changed with the use of some silvicultural treatments, such as spacing, irrigation and fertigation (Sousa et al, 2010). This was not verified for the hybrid Urograndis, which did not show a tendency to decrease in D b with the use of irrigation, thus being considered more stable regarding water availability.…”
Section: Resultsmentioning
confidence: 97%
“…Fertilization may also affect cellulose quality since it changes nutrient rates and the chemical factors used as parameters for timber quality. Sousa et al (2010), Barbosa et al (2014) and others have already shown the influence of fertilization on the timber´s chemical characteristics.…”
Section: Schizolobium Amazonicum Herb (Known As Paricámentioning
confidence: 92%
“…A relevância dos custos nessas operações (Tabela 2) se justifica pela intensa utilização de mão de obra (realizadas de forma semimecanizada e manual) em decorrência da topografia da região. Observouse, também, que as operações de capina e roçada diminuíram gradativamente ao longo do tempo, devido ao crescimento das árvores e, consequente, domínio do espaço pelas copas, diminuindo a competição exercida com as ervas daninhas e, com isso, reduzindo esses custos (Berger et al, 2002;Sousa et al, 2010).…”
Section: Custos De Implantação E Manutenção Colheita E Transporteunclassified